The scale of inland fisheries, can we do better? Alternative approaches for assessment. (26th February 2012) - De Graaf, G.; Bartley, D.; Jorgensen, J.; Marmulla, G.
<x xml:space="preserve">Abstract</x> Abstract The majority of the global inland fisheries catch is obtained in developing countries. However, there are severe constraints in collection of information on inland fisheries leading to doubts over the reliability of the available information at the global and regional scales. A major constraint of data collection is the dispersed characteristics of inland fisheries, which cannot be covered by traditional approaches. Sample‐based monitoring of inland fisheries with an appropriate sample frame will improve the present information on inland fisheries. However, it is argued that further rapid improvement of available information can be obtained by providing assessment tools to a global community of practitioners. One such a tool, a combination of databases making use of Google Earth, analysed in a GIS platform and yield modelling is presented and discussed.